Understanding Antibiotic Use in Companion Animals: A Literature Review Identifying Avenues for Future Efforts - Tompson, Alice C.; Mateus, Ana L. P.; Brodbelt, Dave C.; Chandler, Clare I. R. (Frontiers in Veterinary Science, 2021)
Addressing antibiotic use is a central component of efforts to tackle antimicrobial resistance, a major human and animal health threat. This review seeks to inform antibiotic stewardship initiatives by collating research insights regarding antibiotic use in companion animals, and identifying overlooked avenues for future endeavours. The development of methods enabling the accurate measurement of antibiotic usage in large, population-based samples are described. These have established that antibiotics are frequently used in companion animal care. The clinical, social and economic contexts surrounding these patterns of antibiotic use have also been investigated. Qualitative approaches have identified important factors affecting antibiotic use: interactions with owners, risk management, time pressures, and clinic dynamics. Much of the existing research frames companion animal antibiotic use as the result of choices made by the individuals at the interface of their deployment. Future efforts could look beyond the moment of prescribing to consider the societal structures and networks in which companion animal antibiotic use is entangled. A diversification in research approaches and frameworks through which antibiotic use is understood will facilitate the identification of additional targets for stewardship initiatives beyond providing information and awareness campaigns.